Numerical Study of Transient Bio-Heat Transfer Model With Heat Transfer Coefficient and Conduction Effect in Cylindrical Living Tissue - Luitel, Kabita; Gurung, Dil Bahadur; Khanal, Harihar; Uprety, Kedar Nath (The Nepali Mathematical Sciences Report, 2019)
The human thermal comfort is affected by the body’s heat exchange mechanism conduction, convection, radiation, and evaporation. The mode of heat transfer between the body and environment depends upon the human internal physiological phenomena, together with the boundary conditions. The present paper provides the comprehensive overview of the thermoregulatory system of human body and studies the numerical solution of unsteady-state one dimensional Pennes bio-heat equation with appropriate boundary conditions. The solution is used to observe the temperature profiles at different thermal conductivities, and different heat transfer coefficients in the living tissue at the various time steps. Various physical and physiological factors across the cylindrical living tissue have been incorporated in the model.